CSC799: Usability Engineering / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2017)
Usability engineering is a set of behavioural research methods and techniques that can be applied at every stage of the software development lifecycle. It is used to improve the usability of the developed artefacts. This course describes the concepts, methods and techniques of engineering usability in Web-based environments. Students are required to acquire practical experience in conducting usability studies for Web-based systems that includes designing usability test of such systems, recruit suitable participants, conduct the test, analyse the results and report the findings.